Bimbingan Konseling Terhadap Korban Phedofilia Upaya Meningkatkan Perilaku Adaptif Anak Autisme Melalui Teknik Behavioral Rehearsal - Tambunan, Syafrianto (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
Cases of rape affecting many women have become a problem that is quite alarming, even more sad this rape case does not only affect adult women, but children who are underage even children who are autistic become victims allow them to experience psychological disorders heavy one. This requires special handling from expert institutions or the like to eliminate child trauma and increase the confidence of victims of pedophilia. Behavioral rehearsal technique is a method in which this behavior therapy technique has been developed by psychology and counseling experts to answer and meet the demands of life through adequate guidance and training, people with autism will be motivated to master their life situations, so they feel satisfied to be able to show their superiority in order to eliminate feelings of inferiority, alienation, and lack of confidence. This paper will describe how the solutive steps that will be given to prevent or provide counseling services for victims of Pedhofilia (children with autism) to improve adaptive behavior through counseling techniques, namely Behavioral Rehearsal.